Causes of delay in the construction phase of oil and gas projects in Malaysia - Umeesh Kumar Suppramaniam, S; Ismail, Syuhaida; Suppramaniam, Subaashnii (International Journal of Engineering and Technology, 2018)
The drop-in oil price in recent years has seen the oil and gas projects affected negatively. Thus, most Engineering, Procurement, and Construction (EPC) companies are opting to optimise the project especially in terms of mitigating delays in construction to achieve the project expectation. Delay causes threat to a project objectives in terms of time, cost and quality. It is also a crucial element in deviating from the client’s expectation in terms of productivity, safety and standards. This paper aims at examining the causes of delay in the construction phase of oil and gas projects in Malaysia.  A comprehensive literature review from various sources through books, conference proceedings, the internet, project management journals as well as oil and gas industry journals was made to materialise this paper. There were a few studies that related to this problem and shared a similar view with general construction projects, yet only a fraction of the factors was accepted due to the differences between the two industries. Other variances of the papers included on regional basis or on specific countries. The factors of these attributes were still accepted since it was still applicable to the oil and gas industry and there were not any major variances between countries. The paper has found that there are several significant factors that cause delays in the construction phase of oil and gas projects in Malaysia. The similarity of these delay factors can be grouped into six major groups, namely client, contractor, engineering, external, project and resources. This initial study is based purely on literature review, comparison of similar cases, cross referencing and critical judging. The causes of delay specific to the construction phase in oil and gas projects in Malaysia should be further researched with focus only in the Malaysian projects and industry players.
Keywords: Causes of Delays; Construction Phase; Oil and Gas Projects; Malaysia.